Incidence and mortality trends of stroke and its subtypes among residents in China from 1990 to 2021: an analysis of GBD 2021 data - Wenjiao DONG; Fengxia LAI; Yao LING; Zhimei JIN; Hao CHEN; Danli KONG; Yuanlin DING (Zhongguo gonggong weisheng)
ObjectiveTo analyze the trends in incidence and mortality of stroke, including ischemic stroke (IS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH), among Chinese residents from 1990 to 2021, and to provide a reference for stroke prevention and control strategies in China. MethodsData on the incidence and mortality of stroke, IS, ICH, and SAH among Chinese residents in 1990 and 2021 were obtained from the Global Burden of Disease (GBD) 2021 study. Descriptive analyses were performed using the number of incident cases, incidence rate, number of deaths, and mortality rate. Statistical analyses were conducted using R 4.1.0 software. Trends in the incidence and mortality of stroke and its three subtypes from 1990 to 2021 were analyzed using the overall percentage change and estimated annual percentage change (EAPC). ResultsThe number of incident stroke cases, incidence rate (per 100 000), number of deaths, and mortality rate (per 100 000) among Chinese residents increased from 1 685 762, 143.29, 1 530 590, and 130.10 in 1990 to 4 090 480, 287.51, 2 591 647, and 182.16 in 2021, with overall relative percentage changes of 142.65%, 100.64%, 69.32%, and 40.01%, respectively. Both the incidence and mortality rates of stroke showed a significant increasing trend from 1990 to 2021 (EAPC = 2.02% and 1.01%, both P < 0.001). For IS, the number of incident cases, incidence rate, number of deaths, and mortality rate increased from 761 191, 64.70, 427 970, and 36.38 in 1990 to 2 772 053, 194.84, 1 176 952, and 82.72 in 2021, with overall relative percentage changes of 264.17%, 201.13%, 175.01%, and 127.40%, respectively. Both the incidence and mortality rates of IS showed a significant increasing trend (EAPC = 3.56% and 2.74%, both P < 0.001). For ICH, the corresponding figures increased from 774 012, 65.79, 913 023, and 77.61 in 1990 to 1 173 288, 82.47, 1 322 893, and 92.98 in 2021, with overall relative percentage changes of 51.59%, 25.34%, 44.89%, and 19.81%, respectively. Both the incidence and mortality rates of ICH showed a significant increasing trend (EAPC = 0.40% and 0.50%, both P < 0.01). In contrast, for SAH, the figures decreased from 150 559, 12.80, 189 598, and 16.12 in 1990 to 145 138, 10.20, 91 802, and 6.45 in 2021, with overall relative percentage changes of –3.60%, –20.29%, –51.58%, and –59.96%, respectively. Both the incidence and mortality rates of SAH showed a significant decreasing trend (EAPC = –1.69% and –4.02%, both P < 0.001). In both 1990 and 2021, male residents had higher incidence and mortality rates of stroke, IS, and ICH, as well as a higher incidence rate of SAH compared to females, except for the SAH mortality rate. From 1990 to 2021, the incidence and mortality rates of stroke, IS, and ICH increased in males (EAPC = 2.33% and 1.51%, 3.98% and 3.25%, 0.70% and 1.01%, respectively; all P < 0.05), while the incidence and mortality rates of SAH decreased (EAPC = –1.59% and –3.44%, respectively; both P < 0.05). In females, the incidence and mortality rates of stroke and IS increased (EAPC = 1.61% and 0.40%, 3.15% and 2.12%, respectively; all P<0.05), while the incidence and mortality rates of SAH decreased (EAPC = –1.69% and –4.69%, respectively; both P < 0.05). In both 1990 and 2021, the incidence and mortality rates of stroke and its three subtypes increased with age. The incidence rate of stroke decreased in all age groups from 1990 to 2021 (all P < 0.05), except for the 75 - 79 age group, where the difference was not statistically significant. The incidence rate of IS increased in all age groups (all P < 0.05), except for the age group under 20, which showed a decreasing trend, and the 20 - 24 age group, where the difference was not statistically significant. The mortality rate of IS decreased in all age groups (all P < 0.05), except for the 80 - 84 and ≥ 85 age groups, where the differences were not statistically significant. The incidence and mortality rates of ICH and SAH decreased in all age groups (all P < 0.05). ConclusionsFrom 1990 to 2021, the incidence and mortality rates of stroke, IS, and ICH increased among Chinese residents, while the incidence and mortality rates of SAH decreased. Males and the elderly are high-risk groups for stroke incidence and mortality.